Facile synthesis of a dual-phase CsPbBr3–CsPb2Br5 single crystal and its photoelectric performance. Issue 35 (1st June 2020) - Lin, Congjian; Liu, Lai; Xu, Jinzhuo; Fang, Feier; Jiang, Ke; Liu, Zexiang; Wang, Ye; Chen, Fuming; Yao, Huizhen
Abstract : Dual-phase CsPbBr3 –CsPb2 Br5 single crystal microsheets were synthesized by a simple method based on the coffee ring effect. Abstract : The emerging metal-halide perovskites are promising for next generation optoelectronic devices. Recently, all-inorganic halide perovskites have been developed and show significantly improved stability compared with organic–inorganic hybrid halide perovskites. Here, we report a facile method based on the coffee ring effect of solvents to synthesize dual-phase CsPbBr3 –CsPb2 Br5 single crystal microsheets for the first time. The prepared dual-phase CsPbBr3 –CsPb2 Br5 single crystal is composed of a tetragonal crystalline phase of CsPb2 Br5 and a monoclinic phase of CsPbBr3 according to X-ray diffraction (XRD) patterns. The sharp XRD peaks indicate the high crystallinity of the as-synthesized dual-phase CsPbBr3 –CsPb2 Br5 microsheets. CsPbBr3 is mainly distributed on the edge of the microsheets based on photoluminescence (PL) mapping images. Besides, a photodetector based on the dual-phase CsPbBr3 –CsPb2 Br5 microsheets exhibits good performance with a high on/off photocurrent ratio of 300 and a photoresponsivity of 2.68 mA W −1 . The rise and decay times of the CsPbBr3 –CsPb2 Br5 microsheet photodetector are around 25.3 ms and 29.6 ms, respectively. The experimental results indicate that the dual-phase CsPbBr3 –CsPb2 Br5 microsheet could be a good candidate for the fabrication of high-performance micro photodetectors compatible with practical applications.